2017
DOI: 10.25174/2249-4065/2017/71641
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tillage, Cultivar, Seed Rate and Planting Geometry on Wheat Yield

Abstract: Field experiments were conducted to improve the wheat yield through adjustments in seed rate, spacing and sowing method at Indian Institute of Wheat and Barley Research, Karnal, Haryana during Rabi seasons of 2008-09 to 2012-13. The results showed that by using the precision seed drilling, seed rate from present recommendations of 100 kg/ha can be reduced to 75 kg/ha, however further reduction in seed rate caused yield reductions. If we translate 25% saving across the wheat growing area of India (30 mha) then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…In the present study, the 120 kg ha -1 seed rate produced the highest yield followed by 130, and 100 kg and the lowest was recorded from the 100 kg seed ha -1 . Yield variation due to the variation of seed rate attributed to the production of the highest number of grains (Naseh et al, 2020) in each of the longest spike (Chhokar et al, 2017) and the accumulation of more dry matter content in the grains (Kumar et al, 2018). The optimum spaced plants grown from 120 kg seeds ha -1 had less intra-plant competition, which might contribute to obtaining the bolder seeds in the longest spikes of a higher number m -2 area in this present study.…”
Section: Benefit Cost Ratio (Bcr)mentioning
confidence: 99%
“…In the present study, the 120 kg ha -1 seed rate produced the highest yield followed by 130, and 100 kg and the lowest was recorded from the 100 kg seed ha -1 . Yield variation due to the variation of seed rate attributed to the production of the highest number of grains (Naseh et al, 2020) in each of the longest spike (Chhokar et al, 2017) and the accumulation of more dry matter content in the grains (Kumar et al, 2018). The optimum spaced plants grown from 120 kg seeds ha -1 had less intra-plant competition, which might contribute to obtaining the bolder seeds in the longest spikes of a higher number m -2 area in this present study.…”
Section: Benefit Cost Ratio (Bcr)mentioning
confidence: 99%
“…Additionally, as there is minimum soil disturbance with RDD, it can also be effectively used for cross sowing for higher productivity. Cross sowing in wheat gives the yield advantage over conventional practice (Dhiman et al 1984;Jadho and Nalamwar, 1993;Chhokar et al, 2017). Dhiman et al (1984) reported that four wheat cultivars gave 13-18% higher grain yield when sown by disc drill in cross rows than in one direction only.…”
Section: Demonstrations At Farmers Fieldmentioning
confidence: 99%
“…Major earlier studies about determining optimum plant density emphasized the effect of plant density on the yield and growth of crops (Yan et al, 2016; Chhokar et al, 2017; Allard et al, 2018; Fang et al, 2018; Zhang et al, 2019) and rarely focused on economic analysis of this issue. Based on yield analysis, Chhokar et al (2017) reported that the seed rate of winter wheat can be reduced by 25% for optimum production.…”
Section: Introductionmentioning
confidence: 99%